The role of progressive, therapeutic exercise in the management of upper limb tendinopathies: A systematic review and meta-analysis - Ortega-Castillo, Miguel; Cuesta-Vargas, Antonio; Luque-Teba, Antonio; Trinidad-Fernández, Manuel (Elsevier, 2022)
Among upper limb tendinopathies, rotator cuff-related shoulder pain and lateral elbow tendinopathy are the most representative disorders. Therapeutic exercise arises as an effective approach, but there is no consensus about the optimal progression criteria. Objective: To compare progression criteria and effectiveness of isolated, progressive exercises in the management of upper limb tendinopathies. Additionally, to perform a meta-analysis of pain/function for the selected programs. Design: Systematic Review and Meta-Analysis. Method: Database search of randomized-controlled-trials including progressive exercise was conducted in PubMed and Scopus until October 2020. Meta-analysis’ inclusion criteria were: no data duplicity; 3-months follow-up; comparison between any type of progressive exercise program. Risk of bias was assessed with PEDro score, and level of evidence followed GRADE guidelines. Effect size was calculated with Cohen’s d. Results: Eleven studies were included. GRADE revealed low-quality evidence for meta-analysis of pain during activity (d = 0.29) and function (d = 0.33) at 3 months. Progression criteria were categorised into two divisions, being pain the central concept. Pain (rest/activity/night) and function improved significantly within-group, but between-group changes were heterogeneous. Meta-analysis regarding pain showed good homogeneity with significant, moderate effects (I2 = 20%; p = 0.005; mean d = 0.29); function yielded important heterogeneity with non-significant, moderate effects (I2 = 81%; p = 0.17; mean d = 0.33). Conclusions: Pain was the most frequent benchmark when modulating and progressing the exercises, although other criteria were found such as fatigue or self-perceived ability. Progressive exercise seems effective to manage upper limb tendinopathies, but the superiority of a progression criterion against others remains unclear. (...)
Keywords: Hombros -- Enfermedades; Tendinopathy; Upper limb; Shoulder; Progressive loading; Exercise